Effect of polytetrafluoroethylene binder content on gravimetric capacitance and life cycle stability of graphene supercapacitor - Mohd Abid, Mohd Asyadi 'Azam; Raja Seman, Raja Noor Amalina; Mohamed, Mohd Ambri; Ani, Mohd. Hanafi (Universiti Malaysia Pahang, 2022)
One of the major elements in determining the supercapacitor performance is the development of a nano-layered structure through facilitating the surface-dependent electrochemical reaction processes. Carbon-based nanomaterials especially graphene, has attracted tremendous interest in electrical charge and power sources including supercapacitor because of their exceptional properties, which include high conductivity and large specific surface area. In this paper, the effect of polytetrafluoroethylene (PTFE) binder ratio (1, 5, 10, and 15 wt. %) on the electrochemical performance of graphene supercapacitor are evaluated. In addition, the facile and scalable preparation of graphene electrodes by using low-cost slurry technique is proposed. From the conducted experimental works, it was found that the fabricated graphene electrodes exhibit superior electrochemical properties for supercapacitor applications with a specific gravimetric capacitance of up to 373 F g−1. Moreover, the graphene electrode presented excellent cyclic stability with 99 % specific capacitance retention after 10,000 charge/discharge cycles hence promising for long‐lasting supercapacitors. The outcomes from the deliberated study serve as the basis of knowledge in the development of a cost-effective graphene-based materials production for energy storage devices.